Removal of nitrate from drinking water by using PdCu structured catalysts based on cordierite monoliths - Jaworski, María Angélica (2019)
Structured catalysts were prepared, characterized and evaluated in NO3 - removal from drinking water. Different suspensions containing a previously optimized PdCu/5wt% ZrO2-Al2O3 powder catalyst (hereinafter PdCu/5ZAp) were prepared and deposited on cordierite monoliths by washcoating. The effect of suspension concentration, the particle size, the immersion number, the use of suspension stabilizer agent, and an alumina precoating on the coating adherence and catalytic performance were studied. All the prepared structured catalysts were active for the elimination of NO3 - and presented good selectivity to N2 (> 93%) in synthetic water samples. The catalyst performance was related to the amount of deposited catalyst. The highest activity and the best coating adherence were obtained with the structured catalyst prepared by a single immersion in a 14 wt% concentration suspension, which was obtained from the powder catalyst milled for 10 h and stabilized with colloidal alumina. This catalyst also showed good activity when it was reused for four cycles and when it was evaluated with real water samples.